Cognitive behaviour therapy for health anxiety in medical patients (CHAMP): randomised trial with outcomes to five years - Tyrer,P; Salkovskis,P; Tyrer,H; Wang,D; Crawford,M; Dupont,S; Cooper,S; Green,J; Murphy,D; Smith,G; Bhogal,S; Nourmand,S; et al. (Health Technology Assessment, 2017)
Background: Health anxiety is an under-recognised but frequent cause of distress that is potentially treatable but there are few studies in secondary care. Objective: To determine the clinical effectiveness and cost-effectiveness of a modified form of cognitive-behaviour therapy (CBT-HA) for health anxiety compared with standard care in medical outpatients Design: Randomised controlled trialSetting: Five general hospitals in London, Middlesex and Nottinghamshire Participants:444 patients aged 16-75 seen in cardiology, endocrinology, gastroenterology, neurology and respiratory medicine clinics who scored 20 or more on the Health Anxiety Inventory (HAI), and satisfied diagnostic requirements for hypochondriasis. Those with current psychiatric disorders were excluded but those concurrent medical illnesses were not. Interventions:Cognitive behaviour therapy for health anxiety (CBT-HA): 4-10 one-hour sessions of CBT-HA from a health professional or psychologist trained in the treatment. Standard care was normal practice in primary and secondary care. Main outcome measures: Primary: Researchers masked to allocation assessed patients at baseline, 3m, 6m, 12m, 24m and 5 years. The primary outcome was change in HAI score between baseline and 12 months. Main secondary outcome: Costs of care in the two groups after 24 months and 60 months, change in health anxiety (HAI), generalised anxiety and depression (Hospital Anxiety and Depression (HADS-A and HADS-D) scores, social functioning using the Social Functioning Questionnaire (SFQ), and quality of life using the Euroqol (EQ-5D), at 6, 12, 24 and 60 months, deaths over 5 years. Results: Of 28,991 patients screened over 21m, 5769 had HAI scores of 20 or above. CBT-HA patients (mean sessions 6) had significantly greater improvement in HAI scores than those in standard care at 3m and this was maintained over the five-year period (overall P<0.0001), with no loss of efficacy between 2 and 5 years. Generalised anxiety